Maximizing energy recovery from homeostasis in microbial fuel cell by synergistic conversion of short-chain volatile fatty acid. (September 2019) - Yang, Guang; Wang, Jie; Zhang, Hongwei; Jia, Hui; Zhang, Yang; Cui, Zhao; Gao, Fei
Abstract: In this study, the effect of homeostasis in microbial fuel cell (MFC) on electron transfer and energy recovery from volatile fatty acid (VFA) was investigated. In propionic acid MFC (HPr-MFC), the power density and electricity were enhanced. This was mainly due to the lowest oxidation-reduction potential obtained by the regulation of redox electronic status to accumulate the propionic acid converted into acetic acid. It brought MFC up to homeostasis and remitted electron loss to improve redox property. The energy recovery efficiency improved and electron transfer enhanced and in HPr-MFC with lower internal resistance. These results indicated that the alternation of micro-environment forced microbial to modulate and induced dominant electron transfer competitively. Furthermore, high utilization efficiency and bioconversion efficiency of propionic acid observed in HPr-MFC which different with acetic acid and butyric acid MFCs. The homeostasis in MFC by VFA conversion might helpfully provide a promising way to promote energy recovery. Highlights: The conversion of volatile fatty acid was used to sustain the homeostasis of MFC. The energy can be recovered maximum by HPr and HAc synergistic conversion. The electrogenesis and metabolism pathway in different MFCs were revealed.